2019
DOI: 10.15446/rcp.v28n2.72265
|View full text |Cite
|
Sign up to set email alerts
|

How Do Couples Disagree? An Analysis of Conflict Resolution Profiles and the Quality of Romantic Relationships

Abstract: This study aimed to identify conflict resolution profiles and assess relationship quality levels associated with each profile. The participants were 750 heterosexual couples living in southern Brazil. They filled out measures about conflict resolution strategies, relationship quality, and sociodemographic data. A latent profile analysis was conducted in order to classify participants regarding conflict resolution. Variance and association analyses were also conducted in order to examine relationships between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
8
0
2
Order By: Relevance
“…Some participants also highlighted that sometimes taking a timeout before approaching goal conflict was important suggesting that, also in line with previous research (Holley et al, 2013), avoidance, as long as temporary, may be a successful long-term strategy for negotiating goal conflict. These techniques have been noted in previous prepandemic research (e.g., Delatorre & Wagner, 2019) which suggests conflict negotiation appears to have been largely unchanged despite the pandemic. Together, both quantitative and qualitative results provide evidence of the importance of negotiating goal conflict in relationships that we would expect to be relevant during and beyond the current global health crisis.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 61%
“…Some participants also highlighted that sometimes taking a timeout before approaching goal conflict was important suggesting that, also in line with previous research (Holley et al, 2013), avoidance, as long as temporary, may be a successful long-term strategy for negotiating goal conflict. These techniques have been noted in previous prepandemic research (e.g., Delatorre & Wagner, 2019) which suggests conflict negotiation appears to have been largely unchanged despite the pandemic. Together, both quantitative and qualitative results provide evidence of the importance of negotiating goal conflict in relationships that we would expect to be relevant during and beyond the current global health crisis.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 61%
“…We are aware of no studies that have examined whether successful negotiation of goal conflict predicts support in romantic relationships. However, previous research examining how couples resolve general conflicts has found that more successful negotiation predicts greater relational well-being ( Delatorre & Wagner, 2019 ; Kurdek, 1995 ). Given that successful negotiation of conflict predicts better outcomes and may enable partners to be more supportive, we expect that negotiation of goal conflict will be positively associated with perception of RC support and negatively associated with perception of anti-RC support (H2).…”
Section: Introductionmentioning
confidence: 94%
“…A constructive conflict resolution style will involve open conversation, accepting the partner's point of view, and a commitment to problem-solving. While the destructive conflict resolution style refers to hostile and competitive behavior and avoidance(Rubenstein & Feldman, 1993in Delatorre & Wagner, 2019.…”
mentioning
confidence: 99%